Deteksi Manajemen Laba Melalui Karakteristik Perusahaan dan Beban Pajak Tangguhan - Kisno Kisno; Istianingsih Sastrodiharjo (STIE Indonesia Banking School, 2018)
This study aimed to examine the effect of deferred tax expense and the Firm characteristics in a proxy with ROA and leverage to earning management. Earning management is measured by using discretionary revenue model Stubben (2010), ROA is measured by dividing net income to total assets and leverage is measured by dividing total liabilities to total assets. The data used in this research was secondary data on manufacturing company listed in Indonesia Stock Exchange for the period 2011- 2013. The population was 426 and the samples obtained by using purposive sampling was 45 companies. The analytical method used is multiple linear regression. Statistical test results showed that: 1). Deferred tax expense has a positive effect on Earning management. 2). Firms characteristic in a proxy by ROA has no effect on earnings management. 3). Firm characteristic in a proxy by leverage has a positive effect on earnings management. This paper’s results contribute to an understanding of Earning Management and implication for stakeholders. It suggests that investor shall take more attention when analyzing a company’s financial report, especially on deferred tax expense and leverage because these can be used as the ways to manage the company’s profit.